AN ANALYSIS ON THE ROLE AND FUNCTION OF SINGERS IN WORSHIP: A CASE STUDY AT THE NEW JERUSALEM BETHEL CHURCH INDONESIA - Mabuka, Ariandi Richard; Sri Hartati, R. A. Dinar; Dumais, Franklin (SoCul: International Journal of Research in Social Cultural Issues, 2023)
This research aims to examine the roles and functions of the worship singers at the New Jerusalem Bether Church Indonesia in Kampung Lebo. To achieve this goal, data collection tools such as observation, interviews, literature review, and documentation were employed. The research method used is a qualitative descriptive method, with the objective of identifying the outcomes obtained in the field. In this study, the researcher utilized theories that support the research, serving as the foundation for investigating the roles and functions of singers in worship at the Indonesian Bethel Church in Kampung Lebo. The research has elucidated the roles and functions of singers in the worship of the New Jerusamlem Bether Church Indonesia in Kampung Lebo. The researcher discovered several aspects regarding the roles and functions of singers, including the significant role of backing vocalists in the progression of worship, their ability to assist the song leader in leading worship, the importance of singers being pitch-perfect, their capacity to provide harmony and vocal energy in every song, the ability to transform the worship atmosphere to avoid monotony, guiding the congregation in singing, providing enthusiasm, and making the congregation feel engaged during worship. The data were obtained through interviews with singers and the pastor.